Type XII collagen: distinct extracellular matrix component discovered by cDNA cloning. - Gordon, M K (1987)
We have screened a cDNA library constructed from tendon fibroblast mRNA for the presence of collagenous coding sequences. Nucleotide sequence analysis of one isolated clone, pMG377, reveals that the clone encodes a polypeptide that is homologous to, yet distinctly different from, type IX short-chain collagen polypeptides. The structure of the conceptual translation product of the cDNA is also different from that of all other collagen types. Therefore, we have given the type IX-like collagen chain encoded by pMG377 the designation alpha 1(XII). Ribonuclease protection assays with single-stranded cRNA probes demonstrate that alpha 1(XII) mRNA is present in several tissues such as calvaria, tendon, and sternal cartilage of 17-day-old chicken embryo and in cornea from 6-day-old embryos. Using pMG377 as the hybridization probe, we isolated a fragment of the corresponding gene from a chicken genomic library. Partial nucleotide sequence analysis of the genomic clone DG12 shows that the exon/intron structure of the alpha 1(XII) collagen gene appears to be homologous to that of the alpha 1(IX) and alpha 2(IX) collagen genes. Our data demonstrate that types IX and XII collagen are two homologous members of a family of unique collagenous proteins that show tissue-specific patterns of expression. Based on their structure and the properties of their genes, we conclude that this family of collagens is distinctly different from that of fibrillar collagens.